2017
DOI: 10.1177/1046878117712632
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Gaming Features for Motivating Learners

Abstract: Background. Many learning environments are quickly deserted by learners, even if they are efficient. Gamification of learning environments is a recent approach used to enhance learners' motivation and participation. Aim. One issue with this approach is that people have various expectations and react differently faced with specific game mechanics. So, an important goal lies in automatically adapting game mechanics according to player types. In this paper, we study the gaming features that can be adapted in lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 35 publications
2
65
0
8
Order By: Relevance
“…This point suggests that learners' enjoyment of gaming features does not depend on the impact of the features on their motivation and participation. This result is in line with a previous study that showed that the adaptation process might have a negative impact on the perceived usefulness and fun of adapted gaming features [58]. This observation has strong implications on the adaptation process, as it indicates that adaptation should not be based on explicit learners' choices.…”
Section: Main Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…This point suggests that learners' enjoyment of gaming features does not depend on the impact of the features on their motivation and participation. This result is in line with a previous study that showed that the adaptation process might have a negative impact on the perceived usefulness and fun of adapted gaming features [58]. This observation has strong implications on the adaptation process, as it indicates that adaptation should not be based on explicit learners' choices.…”
Section: Main Findingssupporting
confidence: 91%
“…competition) may be detrimental to others [21]. In this perspective, we conducted a first exploratory study that showed the potential of the adaptation of gaming features for enhancing learners' motivation [22].…”
Section: Impact Of Gamification On Learning Processesmentioning
confidence: 99%
“…Studies: Half of the reviewed papers present studies that rely on an adaptive gamification system in an educational setting [18,19,20,25,28,30,31,34,35,36]. These papers provide valuable results about the impact of adaptive gamification on learner motivation and performance.…”
Section: Architecturesmentioning
confidence: 99%
“…Twelve of the papers reviewed [2,4,6,9,10,11,18,19,20,23,34,35] used the term "game element" to describe the low level implementations they use, such as points, levels, leaderboards, progress. Four papers from the same authors [25,28,29,30] use the term "game features" to present the same level of implementation. Knutas et al [21,22] use the terms "game like elements".…”
Section: Architecturesmentioning
confidence: 99%
“…In the game context, dynamics are described as the engaging and abstract concept part of the game, mechanics as the rules part of the game which must be followed by the player to achieve the desirable results and components as the beginning part of the game which includes the hook and tools that can be employed to incorporate the player into the game (Werbach & Hunter, 2012). Gamification application in training (Alcivar & Abad, 2016), learning motivation (Monterrat, Lavoué, & George, 2017), employee motivation (Dale, 2014), promoting healthy lifestyle (Hamari & Koivisto, 2015) and politics (Mahnic, 2014) has proven to be successful and if designed properly the benefits would be profitable.…”
Section: Game Mechanics Aesthetics and E-consumers: Literature Reviewmentioning
confidence: 99%